Meningkatkan Kesadaran Pentingnya Pendidikan Tinggi Melalui Sosialisasi dan Motivasi Siswa Sekolah Menengah Atas di Lombok Timur - rizki, novia; Hanani, Tri; Priyambodo, Victoria Kusumaningtyas; Sukma, Paradisa; Agustiningsih, Wulandari; Noviawan, Lalu Andika; Prasedya, Tusta Citta Ihtisan Tri; Kartikasari, Nungki (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
Human resources are considered high quality when they have a high level of education. Human resources with a high level of education are expected to be able to respond to the challenges of the times and keep up with global developments in information technology. Higher education is education that is pursued after completing high school. The purpose of the community service activity is to raise awareness of the importance of higher education through socialization and motivation of high school students in East Lombok. The activity method involves three stages: initial observation, implementation of the activity, and evaluation of the activity results. The results indicate that participants felt the socialization and motivation materials presented provided insights into higher education, interactive presentation of materials, and assistance in understanding career choices to determine their major in higher education. In terms of motivation, participants felt more interested in continuing their education to higher education after participating in the socialization and motivation activities. Keywords: human resources; higher education; motivation